2021
DOI: 10.3389/fphar.2021.696802
|View full text |Cite
|
Sign up to set email alerts
|

WTD Attenuating Rheumatoid Arthritis via Suppressing Angiogenesis and Modulating the PI3K/AKT/mTOR/HIF-1α Pathway

Abstract: Background: Wutou Decoction (WTD), as a classic prescription, has been generally used to treat rheumatoid arthritis (RA) for two thousand years in China. However, the potential protective effects of WTD on rheumatoid arthritis and its possible mechanism have rarely been reported.Purpose: The aim of this study was to explore the possible mechanism of WTD against RA and a promising alternative candidate for RA therapy.Methods: A model of collagen-induced arthritis (CIA) was constructed in rats to assess the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The inhibition of various inflammation factors is also the most significant, such as Stat1, Hspb6 and Tgfb. Pi3k-Akt signaling pathway has been profoudly investigated within RA by promoting angiogenesis and activation of fibroblast-like synoviocytes, and testified as reliable therapeutic target [ 19 , 31 , 32 ]. Besides, it participates in aging and ARDs by crosstalk with oxidative stress, DNA damage, apoptosis and inflammation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of various inflammation factors is also the most significant, such as Stat1, Hspb6 and Tgfb. Pi3k-Akt signaling pathway has been profoudly investigated within RA by promoting angiogenesis and activation of fibroblast-like synoviocytes, and testified as reliable therapeutic target [ 19 , 31 , 32 ]. Besides, it participates in aging and ARDs by crosstalk with oxidative stress, DNA damage, apoptosis and inflammation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…225 Abnormal PI3K/ AKT pathway activation will also stimulate the expression of VEGF and HIF-1α to promote angiogenesis, which not only isolates bones from getting nutrients through the synovium but also gets involved in the release of diverse inflammatory mediators, aggravating the condition of RA. [226][227][228] There is evidence indicating that the PI3K/AKT/mTOR pathway participates in the process of RA, the mammalian target of rapamycin (mTOR) inhibits autophagy in FLS, promotes continuous abnormal proliferation of synovial cells, and is also critical for the survival and differentiation of osteoclasts, aggravating RA and mTOR might be a target for RA or other autoimmune diseases. 227,[229][230][231] SYK signaling pathway in RA SYK (spleen tyrosine kinase) is a central molecule of B-cell receptor signaling.…”
Section: Signaling Pathways In the Pathogenesis Of Ramentioning
confidence: 99%
“…Downregulation of hypoxia-inducible factor-1α (HIF-1α) significantly reduces angiogenesis in VEGF-induced rheumatoid arthritis fibroblast-like synoviocytes (RAFLS) in macrophages of the synovial lining ( 60 ). Multiple studies have shown that blocking angiogenic pathways may reduce inflammatory cell infiltration and damage to joints ( 61 , 62 ). In animal models of RA, prophylactic treatment with anti-VEGF antibodies delays the onset, joint swelling, and vascularization in collagen-induced arthritis (CIA) ( 63 ).…”
Section: Il-37 and Aidsmentioning
confidence: 99%